(E)-Selective Defluorinative Diphenothiazination of Trifluoromethyl Styrenes - Yang, Yun; Ebel, Ben; Oppel, Iris M.; Patureau, Frederic W. (Synthesis, 2025)
Alpha-trifluoromethyl styrenes have become a versatile and valuable platform in order to access a wide variety of fluorinated organic motifs over recent years. This is due to their propensity to accommodate diverse defluorinative radical or nucleophilic attacks, which can lead to highly functionalized fluorinated alkenes. In some cases, such as described herein, E/Z selectivity issues can arise. While Zhu showed in 2021 that indole and carbazole nucleophiles lead preferentially to the (Z)-fluoroalkenes, we found that phenothiazines reverse the selectivity toward the (E)-configured diphenothiazinated fluoroalkenes. A scope and diastereoselectivity model for this unexpected reversal is discussed.
Keywords: Phenothiazine; Trifluoromethyl styrene; Fluoroalkene; Defluorinative amination; E/Z selectivity